The USA medical insurance as a stimulating factor to increase labour efficiency - Vitaliia Koibichuk; Bhola Khan; Serhii Drozd (Health Economics and Management Review)
Medical insurance is critical for state labour efficiency. In many countries (including in the United States of America), it is tightly connected to labour, which makes workers have valid insurance policies for free and constant access to medical aid. That strongly secures workers’ health and their high performance. In state-supporting insurance cases, citizens have a common access to medical services (regardless of their employment type). Here, people can be provided with medical aid without worrying about any prices, which keeps their strong health and high productivity skills. Within employment-related medical insurance, it is employers who are fully responsible for their employees’ insurance. As a tangible financial business burden, it may keep workers close to their employment place itself: if resigned, they can lose good medical insurance at all. The medical insurance system is a key and decisive factor to raise labour efficiency. To achieve and secure it, governments should permanently develop affordable and reliable insurance systems. In our research, we chose the following indexes: coverage of state and private insurances, labour efficiency levels, national employment levels, life expectancy, healthcare costs (% of gross domestic product), healthcare costs by volume. We conducted the given study via data normalisation and regression modelling (backward data selection). We applied Multivariate Adaptive Regression Splines (MARS) as a regression-based method to describe non-linear variable relations. Among our engaged methods, there were also bibliography analysis, data processing, systematisation, comparison and logical generalisation. The current research results are relevant for politics and business. Politicians may use them in developing social-economic principles to improve medical insurance and labour efficiency. Enterprises can involve such information to define medical insurance payments for the health and labour efficiency increase among all types of employees in any countries.